2019
DOI: 10.1016/j.ajhg.2019.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Haploinsufficiency of the Notch Ligand DLL1 Causes Variable Neurodevelopmental Disorders

Abstract: Notch signaling is an established developmental pathway for brain morphogenesis. Given that Delta-like 1 (DLL1) is a ligand for the Notch receptor and that a few individuals with developmental delay, intellectual disability, and brain malformations have microdeletions encompassing DLL1, we hypothesized that insufficiency of DLL1 causes a human neurodevelopmental disorder. We performed exome sequencing in individuals with neurodevelopmental disorders. The cohort was identified using known Matchmaker Exchange no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 49 publications
3
40
1
1
Order By: Relevance
“…This agrees with the recent identification of neurodevelopmental disorders apparently not typical to HPE but associated to haploinsufficiency of DLL1. In these patients, intellectual disability and variable brain malformations such as microcephaly occurs (66).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…This agrees with the recent identification of neurodevelopmental disorders apparently not typical to HPE but associated to haploinsufficiency of DLL1. In these patients, intellectual disability and variable brain malformations such as microcephaly occurs (66).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The TBXT gene encodes for T protein, which is crucial for neurulation during embryonic development [ 14 ]. Additionally, the DLL1 gene encodes a Notch ligand protein which is necessary for the Notch signaling cascade involved in neuronal differentiation and migration during the embryonic period [ 15 ]. Haploinsufficiency of one or both of these genes may have resulted in our patient's seizures, structural brain/spine abnormalities, and intellectual disability.…”
Section: Discussionmentioning
confidence: 99%
“…It was also demonstrated that two essential effectors of the Notch signaling are crucial for maintaining the embryonic nervous system structure, keeping the organization and morphology of the cells [ 62 ]. Additionally, pathogenic variants of the Notch ligand Dll1 have recently been suggested as causative of a neurodevelopmental phenotype in a cohort whose individuals presented with developmental delay, intellectual disability, and brain malformations [ 63 ].…”
Section: Lncrnas and Pathways Involved In Non-syndromic Intellectumentioning
confidence: 99%